2015
DOI: 10.1111/jth.12780
|View full text |Cite
|
Sign up to set email alerts
|

Remission of recurrent gastrointestinal bleeding after septal reduction therapy in patients with hypertrophic obstructive cardiomyopathy‐associated acquired von Willebrand syndrome

Abstract: trointestinal bleeding after septal reduction therapy in patients with hypertrophic obstructive cardiomyopathy-associated acquired von Willebrand syndrome. J Thromb Haemost 2015; 13: 191-6.Summary. Background: Gastrointestinal hemorrhage is considered to be a severe complication of von Willebrand disease. The optimal therapy for acquired von Willebrand syndrome and severe gastrointestinal bleeding with hypertrophic cardiomyopathy is undefined. Patients/Methods: Seventy-seven patients (median age, 67 years; int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…A study evaluating patients with hypertrophic cardiomyopathy showed that VWF levels were not predictive of bleeding, but older age, female gender, and higher peak outflow velocity measurements were. 35 A smaller study in mitral regurgitation also showed more bleeding with older age. This study actually showed higher VWF:Ag or VWF:Act levels in the bleeding patients but showed a significantly lower VWF:Act/VWF:Ag ratio and that this ratio decreased with MR severity.…”
Section: Acquired Von Willebrand Syndrome (Avws)mentioning
confidence: 96%
“…A study evaluating patients with hypertrophic cardiomyopathy showed that VWF levels were not predictive of bleeding, but older age, female gender, and higher peak outflow velocity measurements were. 35 A smaller study in mitral regurgitation also showed more bleeding with older age. This study actually showed higher VWF:Ag or VWF:Act levels in the bleeding patients but showed a significantly lower VWF:Act/VWF:Ag ratio and that this ratio decreased with MR severity.…”
Section: Acquired Von Willebrand Syndrome (Avws)mentioning
confidence: 96%
“…We identified patients with cardiac lesions from our multispecialty practice between 2010 and 2016 as previously described 2, 3, 4, 7. The study protocol was approved by the Mayo Foundation Institutional Review Board is registered at clinicaltrials.gov (NCT01334801).…”
Section: Methodsmentioning
confidence: 99%
“…Subjects with LVADs were assumed to have severe lesions. Assessment of the severity of AS, AR, MR, prosthetic valvular dysfunction, and HOCM have been described previously 2, 3, 4, 7. All echocardiograms were reviewed for accuracy (J.L.B.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations